1996
DOI: 10.1111/j.1540-8175.1996.tb00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Echocardiography During Pregnancy

Abstract: Despite continuous improvements in diagnostic cardiology techniques, echocardiography remains the cornerstone for noninvasive cardiovascular assessment of the pregnant woman with heart disease or suspected cardiac abnormality. Reversible physiological cardiac remodeling of pregnancy associated with changes in valve patency or transvalvular flow pattern can be suitably assessed by the complementary use of quantitative pulsed- and continuous Doppler and qualitative color Doppler technology. These techniques are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 33 publications
2
10
0
2
Order By: Relevance
“…Whereas quantitative assessment of the RV using TTE is difficult due to its complex geometry, CMR serves as the gold standard for non-invasive assessment of this chamber due to its higher spatial resolution and low intra- and inter-observer variability [42]. A previous study using TTE demonstrated an increase in RVEDD by 18% during the third trimester [17], which is very similar to the values obtained in our study. Using CMR in our study, we also provide new reference values for an increase in RV volume and mass with preserved RV systolic function during pregnancy.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Whereas quantitative assessment of the RV using TTE is difficult due to its complex geometry, CMR serves as the gold standard for non-invasive assessment of this chamber due to its higher spatial resolution and low intra- and inter-observer variability [42]. A previous study using TTE demonstrated an increase in RVEDD by 18% during the third trimester [17], which is very similar to the values obtained in our study. Using CMR in our study, we also provide new reference values for an increase in RV volume and mass with preserved RV systolic function during pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to previous studies that demonstrated an increase in LA volumes by approximately 30% in the third trimester [10,14,43], our study confirmed LA volume increases of 39% and 50% by TTE and CMR, respectively. Although few studies have examined RA volumes during pregnancy, Campos et al demonstrated a 19% increase in RA dimensions in the third trimester by TTE [17]. Our study demonstrated an increase in RA volume of 34% and 55% by TTE and CMR, respectively.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Studies conducted in normal pregnancy demonstrate an increase in the size of all cardiac chambers, which decline to pre-pregnancy levels after delivery [54]. This is associated with eccentric hypertrophy, and a decrease in LV systolic strain, but stroke volume and stroke work increase, suggesting that the physiologic increase in cardiac output is partly maintained by the increase in chamber dimensions [55].…”
Section: Hypertensive Pregnancy Disorders As a Risk Factor For Futurementioning
confidence: 99%